Resident Vitreoretinal Procedure Volume: Effect of Intravitreal Injections, Region, Program Size, and Vitreoretinal Fellowship and Veterans Affairs Affiliation - Justin, Grant A.; Purt, Boonkit; Abousy, Mya; Qiu, Mary; Fekrat, Sharon; Woreta, Fasika A.; Vajzovic, Lejla (Journal of Academic Ophthalmology, 2023)
Purpose To analyze resident vitreoretinal procedure volume across Accreditation Council of Graduate Medical Education (ACGME) accredited ophthalmology residency programs. We assessed the effect of the increase in intravitreal injections (IVI), geographic region, program size, and Veterans Affairs (VA) and vitreoretinal fellowship affiliation on vitreoretinal procedures.Methods A request was sent to all residency programs in 2018 for their graduating residents' ACGME case logs. Vitreoretinal procedures were defined by ACGME case log categories and included vitreoretinal surgery, peripheral retinal lasers, and IVI. Procedures were categorized by Current Procedural Terminology (CPT) code. Programs were studied by geographic region, program size, and by VA and vitreoretinal fellowship affiliation.Results A total of 38 of 115 (33.0%) programs responded, and 167 residents logged 32,860 vitreoretinal procedures. The median number of retina procedures per resident was 146 (range 36–729). Programs with a vitreoretinal fellowship had a higher average number of vitreoretinal procedures per resident (208.3 vs. 125.0; p = 0.002), but there was no difference between the average number of non-IVI vitreoretinal procedures (60.0 vs. 64.2; p = 0.32). For IVI, VA affiliation (146.6 vs. 71.1; p = 0.02) and vitreoretinal fellowship (149.4 vs. 60.8; p < 0.001) were associated with a greater number. More IVI strongly correlated with a larger total volume of retinal procedures (r = 0.98), and there was no difference across programs for total retinal procedures when IVI was removed.Conclusions The presence of a vitreoretinal fellowship at a residency program had a positive effect on resident total vitreoretinal case volume, but their residents performed more IVI. Programs without vitreoretinal fellowships completed on average more non-IVI procedures.
Keywords: resident education; ACGME; vitreoretinal surgery; intravitreal injection